Peran Mahkamah Konstitusi dalam Menjaga Supremasi Hukum: Studi Komparatif antara Indonesia dan Jerman - Sheptia Damayanti; Intan Miftahurrohmah; Rizky Awaludin; Dede Firmansyah; Ade Fartini (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study analyzes the role of constitutional courts in maintaining the rule of law through a comparative study between the Constitutional Court of Indonesia and the Federal Constitutional Court of Germany (Bundesverfassungsgericht). Using a juridical-normative approach with comparative methods, the research examines legal documents, court decisions, and academic literature related to the rule of law and constitutionalism. Secondary data were sourced from scientific journals, laws, and key court decisions, including the Lüth Case (1958), Brokdorf Case (1985), and Lisbon Treaty Case (2009) in Germany, as well as Indonesia's Constitutional Court Decision No. 91/PUU-XVIII/2020 on the Job Creation Law. The study shows that both countries consider the constitution as the highest norm and position their constitutional courts as guardians of the rule of law. However, Germany’s court enjoys high compliance, whereas Indonesia faces challenges due to weak legal culture, political intervention, and low integrity in law enforcement. The German court has developed the living constitution doctrine, while Indonesia remains more formalistic and reactive. This study concludes that the success of constitutional courts depends on institutional independence, compliance by state institutions, and a societal legal culture that respects the constitution.